Estimation of cause-specific mortality in Rakai, Uganda, using verbal autopsy 1999-2019 - Dorean Nabukalu; Júlia Almeida Calazans; Milly Marston; Clara Calvert; Hadijja Nakawooya; Brendah Nansereko; Robert Sekubugu; Gertrude Nakigozi; David Serwadda; Nelson Sewankambo; Godfrey Kigozi; Ronald H Gray; et al. (Global Health Action)
Background There are scant data on the causes of adult deaths in sub-Saharan Africa. We estimated the level and trends in adult mortality, overall and by different causes, in rural Rakai, Uganda, by age, sex, and HIV status. Objectives To estimate and analyse adult cause-specific mortality trends in Rakai, Uganda. Methodology Mortality information by cause, age, sex, and HIV status was recorded in the Rakai Community Cohort study using verbal autopsy interviews, HIV serosurveys, and residency data. We estimated the average number of years lived in adulthood. Using demographic decomposition methods, we estimated the contribution of each cause of death to adult mortality based on the average number of years lived in adulthood. Results Between 1999 and 2019, 63082 adults (15–60 years) were censused, with 1670 deaths registered. Of these, 1656 (99.2%) had completed cause of death data from verbal autopsy. The crude adult death rate was 5.60 (95% confidence interval (CI): 5.33–5.87) per 1000 person-years of observation (pyo). The crude death rate decreased from 11.41 (95% CI: 10.61–12.28) to 3.27 (95% CI: 2.89–3.68) per 1000 pyo between 1999–2004 and 2015–2019. The average number of years lived in adulthood increased in people living with HIV and decreased in HIV-negative individuals between 2000 and 2019. Communicable diseases, primarily HIV and Malaria, had the biggest decreases, which improved the average number of years lived by approximately extra 12 years of life in females and 6 years in males. There were increases in deaths due to non-communicable diseases and external causes, which reduced the average number of years lived in adulthood by 2.0 years and 1.5 years in females and males, respectively. Conclusion There has been a significant decline in overall mortality from 1999 to 2019, with the greatest decline seen in people living with HIV since the availability of antiretroviral therapy in 2004. By 2020, the predominant causes of death among females were non-communicable diseases, with external causes of death dominating in males.